Ablation of Nampt in AgRP neurons leads to neurodegeneration and impairs fasting‐ and ghrelin‐mediated food intake. Issue 5 (31st March 2021) - de Guia, Roldan Medina; Hassing, Anna S.; Ma, Tao; Plucinska, Kaja; Holst, Birgitte; Gerhart‐Hines, Zach; Emanuelli, Brice; Treebak, Jonas T.
Abstract: Agouti‐related protein (AgRP) neurons in the arcuate nucleus of the hypothalamus regulates food intake and whole‐body metabolism. NAD + regulates multiple cellular processes controlling energy metabolism. Yet, its role in hypothalamic AgRP neurons to control food intake is poorly understood. Here, we aimed to assess whether genetic deletion of nicotinamide phosphoribosyltransferase ( Nampt ), a rate‐limiting enzyme in NAD + production, affects AgRP neuronal function to impact whole‐body metabolism and food intake. Metabolic parameters during fed and fasted states, and upon systemic ghrelin and leptin administration were studied in AgRP‐specific Nampt knockout (ARNKO) mice. We monitored neuropeptide expression levels and density of AgRP neurons in ARNKO mice from embryonic to adult age. NPY cells were used to determine effects of NAMPT inhibition on neuronal viability, energy status, and oxidative stress in vitro . In these cells, NAD + depletion reduced ATP levels, increased oxidative stress, and promoted cell death. Agrp expression in the hypothalamus of ARNKO mice gradually decreased after weaning due to progressive AgRP neuron degeneration. Adult ARNKO mice had normal glucose and insulin tolerance, but exhibited an elevated respiratory exchange ratio (RER) when fasted. Remarkably, fasting‐induced food intake was unaffected in ARNKO mice when evaluated in metabolic cages, but fasting‐ and ghrelin‐induced feeding and body weight gain decreased in ARNKO mice when evaluated outside metabolic cages. Collectively, deletion of Nampt in AgRP neurons causes progressive neurodegeneration and impairs fasting and ghrelin responses in a context‐dependent manner. Our data highlight an essential role of Nampt in AgRP neuron function and viability.